Survei Kegiatan Ekstrakurikuler Olahraga Di Smp Negeri Di Kabupaten Pringsewu Tahun Pelajaran 2019/2020 - Dwiky Dermawan; Reza Adhi Nugroho (Journal of Physical Education, 2020)
This research aims to find out students' interest and how much support from the school to support junior high school extracurricular sports activities in Pringsewu Kota District, Pringsewu Regency. The research method used in this research is quantitative descriptive analysis technique. In this research instrument using a questionnaire or questionnaire (Questionnaires). The results of the study were obtained with good categories as a whole as many as 65 students with a total percentage of 93% in the category of extracurricular sports activities and 14 students with a total percentage of 20% in school infrastructure. Then from the results which stated that it was quite good, it reached 5 students with a percentage of 7% in the category of extracurricular sports activities and 35 students with a total percentage of 50% in school infrastructure. As for the poor classification, there are no extracurricular sports activities and 21 students with a percentage of 30% in school infrastructure.